Single‐step purification of cyclotides using affinity chromatography. Issue 3 (May 2017) - Uddin, Shaikh Jamal; Muhammad, Taj; Shafiullah, Md; Slazak, Blazej; Rouf, Razina; Göransson, Ulf
Abstract: Cyclotides are considered promising scaffolds for drug development owing to their inherent host defence activities and highly stable structure, defined by the cyclic cystine knot. These proteins are expressed as complex mixtures in plants. Although several methods have been developed for their isolation and analysis, purification of cyclotides is still a lengthy process. Here, we describe the use of affinity chromatography for the purification of cyclotides using polyclonal IgG antibodies raised in rabbits against cycloviolacin O2 and immobilized on NHS‐activated Sepharose columns. Cycloviolacin O2 was used as a model substance to evaluate the chromatographic principle, first as a pure compound and then in combination with other cyclotides, that is, bracelet cyclotide cycloviolacin O19 and Möbius cyclotide kalata B1, and in a plant extract. We demonstrate that single‐step purification of cyclotides by affinity chromatography is possible but cross reactivity may occur between homologue cyclotides of the bracelet subfamily.